Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai Dinas Kebudayaan dan Pariwisata Kabupaten Bantaeng - Nuranita Fitriani; M. Ikhwan Maulana Haeruddin; Zainal Ruma; Tenri Sayu Puspitaningsih Dipoatmodjo; Rezky Amalia Hamka (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the influence of work discipline on employee performance at the Bantaeng Regency Culture and Tourism Office. This sampling method uses saturated sampling, which is the entire population of 45 respondents with a quantitative research method. Data collection was obtained through interviews and questionnaire distribution directly (offline). The data analysis techniques used to analyze the relationship between independent variables and dependent variables are validity tests, reliability tests, classical assumption tests, namely normality tests, linearity tests, and homokedasticity tests, hypothesis tests used Partial tests (t-test), and determination coefficients (R2 test). The results of this study show that work discipline has a positive and significant effect on the performance of employees at the Bantaeng Regency Culture and Tourism Office.